2021
DOI: 10.3390/horticulturae7080221
|View full text |Cite
|
Sign up to set email alerts
|

Corn Cob-Derived Biochar Improves the Growth of Saline-Irrigated Quinoa in Different Orders of Egyptian Soils

Abstract: Biochar is one of the important recycling methods in sustainable development, as it ensures the transformation of agricultural wastes into fertilizers and conditioners that improve soil properties and fertility. In the current study, corn cob-derived biochar (CB) was used to reduce the negative effects of saline water on quinoa (Chenopodium quinoa cv. Utosaya Q37) grown on Aridisols and Entisols, which are the major soil groups of Egyptian soils. Quinoa plants were cultivated in pot experiment and were irrigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 59 publications
3
15
2
Order By: Relevance
“…Consequently, those parameters were high in the soil treated with biochar, and the increase was more evident with high rates of biochar application. These results were compatible with those obtained by [31][32][33]. The decrease in soil salinity values resulting from 2% GB 400 may be attributable to salt adsorption by biochar, maintenance without an increase in soil solution, and/or downward movement of saline water resulting in a lower EC value [3,[34][35][36].…”
Section: Biochar Effectsupporting
confidence: 88%
“…Consequently, those parameters were high in the soil treated with biochar, and the increase was more evident with high rates of biochar application. These results were compatible with those obtained by [31][32][33]. The decrease in soil salinity values resulting from 2% GB 400 may be attributable to salt adsorption by biochar, maintenance without an increase in soil solution, and/or downward movement of saline water resulting in a lower EC value [3,[34][35][36].…”
Section: Biochar Effectsupporting
confidence: 88%
“…Molasses stimulates the production of organic acids in the soil which helps to decrease soil pH. These results are compatible with those obtained by Awad et al (2021) and Awad et al, (2020a) who reported that the application of humic and sugar can vinasse decrease the pH value of different soils. The results showed a decrease in electrical conductivity (EC) as a result of organic amendments application, and the effect was more pronounced with the high rate.…”
Section: Soil Chemical Propertiessupporting
confidence: 91%
“…This result may be due to the high organic matter content of these amendments which was more declared with the high rate. Similar results were obtained by Ali et al (2021), Awad (2016), Rekaby et al (2020), andRekaby et al (2021) who concluded that the organic matter gradually increased with increasing the organic materials application level compared to control in the tested soils. Also, Chen et al (2014) indicated that the addition of humic acid could enhance the content of soil organic matter.…”
Section: Soil Chemical Propertiessupporting
confidence: 87%
“…Various mechanisms can control drought stress, including grafting and genetic breeding. Lately, the grafting system has been used to maintain drought stress in numerous plant types [ 35 , 36 ]. To our knowledge, the current study is the first to explore and choose five rootstock plants tolerant to water deficits, which may cause drought tolerance in cucumbers by activating the stress-responsive gene expression and antioxidant enzyme system [ 4 ].…”
Section: Discussionmentioning
confidence: 99%